Effect of Pd doping on the activity and stability of directly assembled La0.95Co0.19Fe0.76Pd0.05O3-δ cathodes of solid oxide fuel cells - Li, N.; Ai, N.; He, S.; Cheng, Y.; Rickard, William; Chen, K.; Zhang, T.; Jiang, S. (Elsevier BV * North-Holland, 2018)
Sr doping is a common strategy to enhance the electrocatalytic activity of perovskite cathode materials of solid oxide fuel cells (SOFCs), but the tendency of Sr surface segregation, chemical incompatibility with yttria-stabilized zirconia (YSZ) and interaction with volatile contaminants such as chromium in SOFC stacks lead to a loss of long-term cell performance. Herein, a Sr-free and Pd-doped La 0.95 Co 0.19 Fe 0.76 Pd 0.05 O 3-d (LCFPd) cathode is directly assembled on a barrier-layer-free YSZ electrolyte cell without conventional high temperature pre-sintering. The cell with the directly assembled LCFPd-GDC (gadolinium-doped ceria) composite cathode exhibits a peak power density of 1035 mW cm - 2 and excellent operation stability at 750 °C for 200 h. Cathodic polarization significantly enhances the electrode/electrolyte interface contact, indicated by the substantial decrease of cell ohmic resistance from 0.28 O cm 2 to 0.14 O cm 2 after polarization at 500 mA cm - 2 and 750 °C for 120 h. Detailed elemental analysis indicates that doped Pd could be segregated on the electrode surface under fuel cell operation conditions, which significantly enhances the electrocatalytic activity for the O 2 reduction reaction. This study provides new strategy to develop cobaltite based perovskite materials directly on YSZ electrolyte.